2011
DOI: 10.1007/s12311-011-0292-z
|View full text |Cite
|
Sign up to set email alerts
|

Spinocerebellar Ataxia Types 1, 2, 3 and 6: the Clinical Spectrum of Ataxia and Morphometric Brainstem and Cerebellar Findings

Abstract: To assess the clinical spectrum of ataxia and cerebellar oculomotor deficits in the most common spinocerebellar ataxias (SCAs), we analysed the baseline data of the EUROSCA natural history study, a multicentric cohort study of 526 patients with either spinocerebellar ataxia type 1, 2, 3 or 6. To quantify ataxia symptoms, we used the Scale for the Assessment and Rating of Ataxia (SARA). The presence of cerebellar oculomotor signs was assessed using the Inventory of Non-Ataxia Symptoms (INAS). In a subgroup of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
67
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 39 publications
6
67
1
Order By: Relevance
“…These findings were observed in only one out of 42 German patients 10 . This observation is in line with the viewpoint shared by Jacobi et al among other groups, who state that there is a significant overlapping among different SCA, impeding purely clinical based diagnoses 11 . Stevanin, Dürr and Brice 12 suggested that BE is not common among non-Portuguese Western European SCA3 patients, and might, therefore, be related to ethnic background.…”
Section: Discussionsupporting
confidence: 89%
“…These findings were observed in only one out of 42 German patients 10 . This observation is in line with the viewpoint shared by Jacobi et al among other groups, who state that there is a significant overlapping among different SCA, impeding purely clinical based diagnoses 11 . Stevanin, Dürr and Brice 12 suggested that BE is not common among non-Portuguese Western European SCA3 patients, and might, therefore, be related to ethnic background.…”
Section: Discussionsupporting
confidence: 89%
“…GEN is almost universal in SCA 6 (7,2022). The infrequency of GEN in SCA 2 has been noted in other clinical studies (11,12). Eye movement recordings have either not detected GEN in SCA 2 (10) or found it in fewer than 50% of subjects (7,20).…”
Section: Discussionsupporting
confidence: 68%
“…SCAs are associated with a variety of abnormalities in eye movements; some of these results from abnormalities in cerebellar control, whereas others reflect extracerebellar pathology. Previous publications have documented the type of abnormalities noted in families examined during gene identification studies, in small scale reports using eye movement recordings (410) and in larger patient cohorts of SCA subjects (11,12). We summarize the findings of bedside ocular motor examination performed prospectively in a large cohort of patients with SCAs 1, 2, 3, and 6 and examine factors that may influence their presence.…”
mentioning
confidence: 99%
“…1 Gliosis has been observed also in the thalamus, globus pallidus, and subthalamic region. 1 MR imaging shows loss of bulk of the brain stem and cerebellum in presymptomatic and early symptomatic SCA2 gene carriers [4][5][6] and circumscribed atrophy of the frontal, parietal, and temporal cortex, the thalamus, and frontal and temporal WM in more advanced cases. 19,45,46 MR imaging can also show diffuse high signal intensity of the brain stem and cerebellar WM with sparing of the corticospinal tracts in proton-attenuation and T2-weighted images.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 MR T1-weighted imaging enables in vivo detection of brain stem and cerebellar atrophy in patients with SCA2 in crosssectional [4][5][6] and longitudinal 7 studies. Recently, DWI and DTI have enabled quantitative assessment of the microstructural changes in brain tissue that result from neurodegenerative diseases.…”
mentioning
confidence: 99%